Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Persetubuhan - Siti Khodijah; Ainul Azizah; Aan Efendi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In practice, children as victims of the crime of sexual intercourse find it difficult to fight for their rights in the form of legal protection as victims. Especially in the case of Cassation Decision Number 281 K/Pid.Sus/2019 and Appeal Decision Number 155/Pid.Sus/2018/PT.Mdn which are used as research objects, it is necessary to examine to what extent the legal protection of children's rights as victims of criminal acts is fulfilled. In this problem, it was discovered that regulations at that time did not really focus on victims, the criminal justice system at the time of the case process was still focused on the defendant as the perpetrator of the crime, while the victim was only passive because his legal interests were already represented by investigators and public prosecutors. Moreover, it was made worse by the weak regulations that existed at that time, causing the interests of children as victims of criminal acts to be neglected. However, if we look at future legal policies or existing regulations that have emerged at this time, it turns out that we have a strong direction towards legal protection for children as victims of criminal acts of sexual intercourse. At least the victim can play an active role in fulfilling and achieving legal protection, and is supported by criminal objectives and guidelines that are very different from the criminal objectives that were in effect at the time the case took place.